Types and Motives of Using Euphemism By Minangkabau Teenagers and Adults in Pariaman - Rima Khairatur Ramadhani; Jufrizal Jufrizal (Universitas Negeri Padang, 2022)
This research aimed at finding the types and motives of using euphemism by Minangkabau teenagers and adults in Pariaman. The type of this research was descriptive-qualitative research. The data were euphemism uterances used by the informants. The informants of this research were Minangkabau native speakers. The data were collected by using the observation. The researcher found there were four types and two motives of euphemisms used by Minangkabau teenagers in Pariaman. Types of euphemisms were part of body, thing and animal, event, characteristics and situation while the motives of euphemisms were to polite the speech and hide something. Meanwhile, there were seven types and three motives of euphemisms used by Minangkabau adults. Types of euphemisms were part of body, thing and animal, event, characteristics and situation, occupation, disease, and activity euphemism. The motives included to polite the speech, hide something and refuse hazard.